2014
DOI: 10.7205/milmed-d-13-00324
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Evacuations From Areas of Operation to the Spanish Role 4 Medical Treatment Facility (2008–2013)

Abstract: Since 1987, the Spanish Armed Forces have deployed their troops in a multitude of conflicts and natural disasters worldwide. The Spanish Military Medical Corps has the ability to deploy Role 1, Role 2, and one Role 3 medical treatment facilities. It also has a Role 4 in operation, the "Gómez Ulla" Central Hospital of Defense, in Madrid. The aim of this study is to describe the type of Spanish casualties evacuated from different areas of operation to the Role 4 from 2008 to 2013. A retrospective, cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Authors of this paper have observed an even greater disproportion in the morbidity and traumatic profiles between Polish and Spanish military personnel. The research study conducted by Suay et al [7] focusing on 232 Spanish soldiers who were medically evacuated from operational areas (mostly from Afghanistan: 47% and Lebanon: 19%) to Spain (Central Hospital of Defence in Madrid, Role 4) between 2008 and 2013 indicated that 91% of the soldiers required medical evacuation out of the theatre due to diseases and non-battle injuries (diseases: 54%, traffic accident injuries: 23%, sports injuries: 14%). Battle injuries were the cause of only 9% of all medical evacuations (5% were due to shell fragment wounds suffered in IED explosions, 4% were due to gunshot wounds).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors of this paper have observed an even greater disproportion in the morbidity and traumatic profiles between Polish and Spanish military personnel. The research study conducted by Suay et al [7] focusing on 232 Spanish soldiers who were medically evacuated from operational areas (mostly from Afghanistan: 47% and Lebanon: 19%) to Spain (Central Hospital of Defence in Madrid, Role 4) between 2008 and 2013 indicated that 91% of the soldiers required medical evacuation out of the theatre due to diseases and non-battle injuries (diseases: 54%, traffic accident injuries: 23%, sports injuries: 14%). Battle injuries were the cause of only 9% of all medical evacuations (5% were due to shell fragment wounds suffered in IED explosions, 4% were due to gunshot wounds).…”
Section: Discussionmentioning
confidence: 99%
“…Battle injuries were the cause of only 9% of all medical evacuations (5% were due to shell fragment wounds suffered in IED explosions, 4% were due to gunshot wounds). Other than combat-related causes of medical evacuations included psychiatric disorders, such as adaptation disorders, anxiety, and depression (12%), cardiovascular diseases (9%), gynaecological diseases/ /conditions (7%), neurological (6%), gastrointestinal (6%), urogenital diseases (5%) [7].…”
Section: Discussionmentioning
confidence: 99%